Double vision - Barker Pat (Hamish Hamilton, 2003)
"Insomnia, exhaustion, recurring nightmares - Stephen Sharkey is suffering the after-effects of his career as a war reporter, most recently in Afghanistan, where Ben Frobisher, war photographer and friend, has been shot dead on assignment. Hanging up his flak jacket and turning his back on the everyday reality of war, Stephen moves into a quiet and peaceful cottage in the north of England. It seems the perfect environment in which to write his book on the representations of war - a book that will be based largely on Ben Frobisher's work." "Here Stephen meets Kate Frobisher, Ben's widow, and the mysterious Peter Wingrave, who seems to generate nothing but unease in those around him - and Justine, a woman twenty years Stephen's junior, with whom he soon finds himself involved. Even far from the war-torn countries he has left behind, Stephen's supposed isolation offers no protection from other people's suffering or the shattering effects of human brutality."--Jacket